Research paradigms and the politics of nursing knowledge: A reflective discussion - Nairn, Stuart (Nursing philosophy, 2019)
A standard view would suggest that research is a neutral apolitical activity. It neutralizes external pressures by its fidelity to robust scientific methods. However, politics is an inevitable part of human knowledge. Our knowledge of the world is always mediated by human priorities. What matters is therefore a contested and political debate rather a neutral accumulation of factual data. How researchers manage this varies. Research paradigms are one way in which research engages with knowledge. They frame knowledge within epistemological and ontological philosophies. In this paper, I will explore this view in relation to neo-positivism, qualitative research, Foucault and critical realism. I will argue that if nursing knowledge is to be effective it needs to acknowledge the political, particularly in the context of neoliberalism. Healthcare systems are having to cope with a social world increasingly dominated by market fundamentalism, extreme levels of inequality and a rise in xenophobia. These forces are undermining the provision of ethically sound health care, misdirecting research practice and contributing to a discourse of dehumanization. These forces need to be challenged politically and I will argue that epistemologically diverse approaches, alongside a realist ontology can provide a way forward for nursing research.